Fusarium keratitis in Brazil: genotyping, in vitro susceptibilities, and clinical outcomes - Oechsler RA (Dove Medical Press, 2013)
Rafael A Oechsler,1 Tiago M Yamanaka,1 Paulo JM Bispo,1 Juliana Sartori,1 Maria Cecilia Zorat Yu,1 Analy Salles A Melo,2 Darlene Miller,3 Ana Luisa Hofling-Lima1 1Ophthalmology Department, 2Division of Infectious Diseases, Internal Medicine Department, Federal University of São Paulo, São Paulo, Brazil; 3Bascom Palmer Eye Institute, Miller School of Medicine, University of Miami, Miami, FL, USA Background: The purpose of this paper is to describe clinical characteristics and determine correlations between clinical outcomes and antifungal susceptibility among molecularly characterized ocular Fusarium isolates in Brazil. Methods: Forty-one Fusarium isolates obtained from 41 eyes of 41 patients were retrieved from the ophthalmic microbiology laboratory at São Paulo Federal University and grown in pure culture. These isolates were genotyped and antifungal susceptibilities determined for each isolate using a broth microdilution method. The corresponding medical records were reviewed to determine clinical outcomes. Results: The 41 isolates were genotypically classified as Fusarium solani species complex (36 isolates, 88%), Fusarium oxysporum species complex (two isolates, 5%), Fusarium dimerum species complex (one isolate, 2%) and two isolates that did not group into any of the species complexes. Final best corrected visual acuity varied from 20/20 to light perception and was on average 20/800 (logarithm of the minimum angle of resolution (LogMAR) 1.6). A history of trauma was the most common risk factor, being present in 21 patients (51%). Therapeutic penetrating keratoplasty was necessary in 22 patients (54%). Amphotericin B had the lowest minimum inhibitory concentration for 90% of isolates (MIC90) value (2 µg/mL) and voriconazole had the highest (16 µg/mL). There was an association between a higher natamycin MIC and need for therapeutic penetrating keratoplasty (Mann–Whitney test, P < 0.005). Conclusion: Trauma was the main risk factor, and therapeutic penetrating keratoplasty was necessary in 54% of patients. Amphotericin B had the lowest MIC90 (2 µg/mL) of the three antifungal agents tested. There was an association between higher natamycin MIC levels and corneal perforation, emphasizing the need for antifungal susceptibility testing and tailoring of antifungal strategies. Keywords: keratitis, Fusarium species, genotyping, antifungal, clinical outcome